Applications of chitosan-based carrier as an encapsulating agent in food industry. (February 2022) - Maleki, Gisoo; Woltering, Ernst J.; Mozafari, M.R.
Abstract: Background: Certain food bioactives and nutraceuticals need to be preserved from environmental factors such as pH, light, oxygen, temperature, and enzymatic degradation because they are chemically or physically instable. Moreover, these compounds may be degraded in gastrointestinal system and are not absorbed in body. Being a novel technique, encapsulation suggested effective solution to the limitations of delivering intact bioactive ingredients to the target sites. Chitosan has been extensively valued as a delivery system for bioactive ingredients. Scope and approach: In this review article, we discuss the potential applications of chitosan-based carriers as encapsulating agent in food industry. Chitosan alone or modified chitosan particles have been extensively used as a coating on liposome and alginate beads, as well as a delivery system for bioactive ingredients such as essential oils, flavor, vitamins, antioxidants, and probiotics. Key findings and conclusions: Chitosan is a cationic natural polysaccharide which has emerged as a suitable carrier in delivering nutraceuticals as it is non-toxic, biodegradable and biocompatible. Chitosan encapsulation can protect bioactive ingredients from extreme conditions such as pH and temperature. Chitosan capsules have proved to be suitable carriers for essential oils, flavors, vitamins, antioxidants, and probiotics. Highlights: Food bioactives need to be protected from environmental conditions due to their chemical and physical instability. Encapsulation provides effective solution for limitations of delivering intact bioactive ingredients to the target sites. Chitosan has been extensively valued as a delivery system for bioactive ingredients. Chitosan is being used as a coating on carrier systems and as a delivery system for food bioactive ingredients. In this review we discuss potential applications of chitosan-based carriers as encapsulating agent in food industry.